THE INFLUENCE OF INVESTMENT KNOWLEDGE, INVESTMENT MOTIVATION AND FINANCIAL LITERATURE ON INVESTMENT INTEREST (CASE STUDY IN INDONESIA STUDENTS WHO HAVE INVESTED) - Sumaiya, Annisa; Meliala, Melinda S; Setiawan, Teguh Agus (Universitas Mercu Buana, 2022)
ABSTRACTThe purpose of this study is to determine whether there is a relationship between investment interest based on investment knowledge, investment motivation and financial literacy. The investment interest variable is the dependent variable. Meanwhile, investment knowledge, investment motivation and financial literacy are independent variables in this study. Processing research data using multiple regression method through SPSS software. Based on the results and conclusions of this study, investment knowledge does not have a significant effect on student investment interest in the capital market. Meanwhile, investment motivation and financial literacy have a significant influence on investment interest in the capital market.